2011
DOI: 10.1371/journal.pone.0021718
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Factors Associated with the Utilization of Community Health Centers for Managing Hypertensive Patients in Chengdu, China

Abstract: BackgroundFor decades the development of community health services has been emphasized in China to cope with the growing burden of chronic diseases by providing basic medical services. This survey aims at investigating factors associated with the use of Community Health Centers (CHCs) for the management of hypertensive patients in Chengdu, China.MethodsWe used a systematic sampling method to select 2,030 patients with hypertension or diabetes registered in 29 CHCs in Chengdu in 2007. Researchers interviewed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…with performing HBPM at least once a week reported by 52% in Zhejiang [18], 36.9% in Chengdu [19] and 42.8% in Beijing [20]. The present study showed that HBPM was performed by around 47.8% of patients in Beijing, 19.8% in Jiangsu and 14.7% in Shandong.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…with performing HBPM at least once a week reported by 52% in Zhejiang [18], 36.9% in Chengdu [19] and 42.8% in Beijing [20]. The present study showed that HBPM was performed by around 47.8% of patients in Beijing, 19.8% in Jiangsu and 14.7% in Shandong.…”
Section: Resultssupporting
confidence: 51%
“…Reasons for poor adherence to HBPM may include: 1) patients lack adequate knowledge about the optimal frequency of HBPM [19,23,28]; 2) presence of barriers to conducting regular HBPM for patients;…”
Section: Resultsmentioning
confidence: 99%
“…Aging of the population, prevalence of chronic disease had brought higher health care need in community [ 16 ]. The policy incentives including the privilege of 20% more reimbursement than hospital and essential medicines dispensed at the procurement price made CHSIs more attractive, especially for patients with low income [ 17 , 18 , 19 ]. Let alone the geographical convenience as well as better availability and accessibility than hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, community clinics and stores are an accessible resource for measuring BP levels. Although the utilization of BP monitors in community health centers for hypertensive patients has been previously assessed [27], there are little data about the use of monitors stationed in stores. Further investigation is needed to determine whether monitors available in stores are reliable and easily accessible for BP measurement as well as whether these monitors can be used for hypertension management in rural areas.…”
Section: Discussionmentioning
confidence: 99%